2007
DOI: 10.1007/s10560-007-0083-z
|View full text |Cite
|
Sign up to set email alerts
|

Youth Sexual Exploitation on the Internet: DSM-IV Diagnoses and Gender Differences in Co-occurring Mental Health Issues

Abstract: This paper explores conventional (non-Internet-related) mental health issues and DSM-IV diagnoses seen among a sample of 512 youth receiving mental health services for an Internet-related problem, with particular attention to victims of online sexual exploitation. Youth victims of online sexual exploitation were more likely to have a post-traumatic stress disorder than youth with other Internet-related problems. Specific attention was given to differences among subgroups of female and male youth victims of onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 17 publications
(17 reference statements)
2
31
0
2
Order By: Relevance
“…PTSD has been associated with unwanted sexual solicitations (Fitzgerald et al, 1997), bullying (Spence Laschinger and Nosko, 2015), and explicit content exposure (Clohessy and Ehlers, 1999) in offline contexts. While some research has examined post-traumatic stress in online contexts, this research examined severe trauma related to cyberbullying (Ranney et al, 2016) and online sexual exploitations (Wells and Mitchell, 2007) in specific high-risk contexts. For instance, Ranney et al (2016) surveyed youth who sought out emergency medical services, while Wells and Mitchell (2007) LGBT community (Beckerman and Auerbach, 2014) and teens at high risk of psychosis (Magaud et al, 2013).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…PTSD has been associated with unwanted sexual solicitations (Fitzgerald et al, 1997), bullying (Spence Laschinger and Nosko, 2015), and explicit content exposure (Clohessy and Ehlers, 1999) in offline contexts. While some research has examined post-traumatic stress in online contexts, this research examined severe trauma related to cyberbullying (Ranney et al, 2016) and online sexual exploitations (Wells and Mitchell, 2007) in specific high-risk contexts. For instance, Ranney et al (2016) surveyed youth who sought out emergency medical services, while Wells and Mitchell (2007) LGBT community (Beckerman and Auerbach, 2014) and teens at high risk of psychosis (Magaud et al, 2013).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…Victims or survivors of sexual exploitation and trafficking maintain increased rates of mental health issues such as depression and posttraumatic stress disorder (PTSD) and have elevated rates of trauma (Muftic & Finn, 2013; Pierce, 2012; Reid, 2011; Twill, Green, & Traylor, 2010; Wells & Mitchell, 2007). These are important risks and consequences of sexual exploitation because they profoundly affect individuals’ experiences during sexual exploitation and any assistance they may subsequently seek.…”
Section: Microlevel: Risks and Consequences Of Sexual Exploitationmentioning
confidence: 99%
“…Several studies of 100 participants or fewer showed that female victims of sexual exploitation experience rates of PTSD ranging from 27% (Wells & Mitchell, 2007) to 50% (Twill et al, 2010). Similarly, these types of studies showed depression rates of up to 60% (Roe-Sepowitz, 2012).…”
Section: Microlevel: Risks and Consequences Of Sexual Exploitationmentioning
confidence: 99%
“… The lack of visual cues in cyber space that may assist them in making judgments about the suitability, trustworthiness and sincerity of those they are communicating with (Wells & Mitchell 2007); and  Children are often at a stage of learning how to communicate effectively and hence less likely to be as socially skilled as adults (Lamb & Brown 2006;Olson, Daggs, Ellevold & Rogers 2007).…”
Section: Absence Of Capable Guardianshipmentioning
confidence: 99%